Hexafluoropropylene oxide dimer acid (GenX) exposure induces apoptosis in HepG2 cells - Hee Joon Yoo (Elsevier, 2021)
Hexafluoropropylene oxide dimer acid, also known as GenX, is a poly- and perfluoroalkyl substance (PFAS). PFASs are nonvolatile synthetic substances that can be readily disseminated into the environment during processing and use, making them easy to implement in the soil, drinking water, and air. Compared to other PFASs, GenX has a comparatively short carbon chain length and is expected to have a lower tendency to accumulate in humans; therefore, GenX has recently been used as a substitute to other PFASs. However, the mechanisms underlying GenX action and intoxication in humans remains unclear. In this study, the apoptotic capacity of GenX in human liver cells was investigated. When representative human-derived liver cells (HepG2 cells) were treated with GenX for 12 h, cell viability was reduced, and apoptosis was greatly increased. In addition, GenX increased the generation of intracellular reactive oxygen species (ROS), indicating the induction of oxidative stress in a dose-dependent manner. GenX treatment increased the expression of major apoptosis-related genes relative to the untreated control group. This research indicates that GenX causes apoptosis through ROS mediation in HepG2 cells, which may expand our knowledge of the molecular and toxicological mechanisms of GenX.